2004
DOI: 10.1128/jb.186.16.5384-5391.2004
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-Acetic Acid Biosynthesis Is Deficient in Gluconacetobacter diazotrophicus Strains with Mutations in Cytochrome c Biogenesis Genes

Abstract: Gluconacetobacter diazotrophicus is an endophyte of sugarcane frequently found in plants grown in agricultural areas where nitrogen fertilizer input is low. Recent results from this laboratory, using mutant strains of G. diazotrophicus unable to fix nitrogen, suggested that there are two beneficial effects of G. diazotrophicus on sugarcane growth: one dependent and one not dependent on nitrogen fixation. A plant growth-promoting substance, such as indole-3-acetic acid (IAA), known to be produced by G. diazotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(109 citation statements)
references
References 55 publications
5
97
0
7
Order By: Relevance
“…These organisms seem to have important roles in plant development and health because they can promote plant growth by nutrient assimilation or phytohormone production. In addition they can act as antagonists against phytopathogens through the production of antibiotics or siderophores, nutrient competition and induction of systemic disease resistance (Kunoh 2002;Lee et al 2004;Bailey et al 2006;Hasegawa et al 2006;Meguro A 2006;Conn 2008;Qin et al 2011). It has also reported that several actinobacteria discovered from plants produce different kinds of secondary metabolites, which might be promising sources of novel antibiotics and growth regulators of other organisms (Castillo et al 2006;Hasegawa et al 2006;Qin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These organisms seem to have important roles in plant development and health because they can promote plant growth by nutrient assimilation or phytohormone production. In addition they can act as antagonists against phytopathogens through the production of antibiotics or siderophores, nutrient competition and induction of systemic disease resistance (Kunoh 2002;Lee et al 2004;Bailey et al 2006;Hasegawa et al 2006;Meguro A 2006;Conn 2008;Qin et al 2011). It has also reported that several actinobacteria discovered from plants produce different kinds of secondary metabolites, which might be promising sources of novel antibiotics and growth regulators of other organisms (Castillo et al 2006;Hasegawa et al 2006;Qin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It was possible that conversion of the mung bean sprout extract and fish extract to tryptophan was much lower than 200 ppm and consequently the production IAA were about 25 ppm. According to Lee et al (2004), in presence of higher concentration of tryptophan, the microbes release greater quantities of IAA and related compounds. The using of tryptophan in this work was as positive control.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that the isolates recovered from in vitro yacon cultures were endophytes except for F. oryzihabitans, which grew endo and epiphytically. Several reports indicate that plant growth promoting bacteria are beneficial endophytes growing in association with the host [21][22][23]. Among the S. sonchifolius isolates, Microbacterium imperiali and Sphingomonas paucimobilis were the highest IAA producers ( Table 4).…”
Section: Isolation and Identification Of Epiphytic And Endophytic Bacmentioning
confidence: 99%